The Impact of Zakat Education, Religious Awareness, and Program Socialization on Participation of ASN Muzakki: A Study at BAZNAS (BAZIS) of Administrative City, West Jakarta - Ahmad Ruyat Ismail; Abdul Ghoni (AHKAM, 2026)
The participation of civil servants, or State Civil Apparatus (ASN), in professional zakat is a strategic factor in optimizing zakat management through official state institutions, particularly BAZNAS (BAZIS) of DKI Jakarta Province. However, ASN participation in professional zakat, especially in West Jakarta Administrative City, remains low and is constrained by several institutional and socio-religious challenges. This study aims to analyze the influence of zakat education, religious awareness, and program socialization on ASN muzakki participation within the West Jakarta Administrative City Government. The study employed a mixed-methods approach with an explanatory sequential design, involving 377 respondents and in-depth interviews with three informants consisting of socialization and education program organizers and ASN who serve as muzakki. The findings indicate that zakat education, religious awareness, and program socialization simultaneously exert a significant influence on ASN professional zakat participation, with a collective effect of 66.3%. Among the three variables, program socialization provides the strongest contribution, followed by zakat education and religious awareness. The study concludes that systematic zakat education, the strengthening of religious values, and relevant socialization programs involving key figures are effective strategies for increasing ASN participation in professional zakat. These findings contribute to the development of evidence-based zakat collection policies and provide practical implications for BAZNAS (BAZIS) of DKI Jakarta Province in designing more responsive programs aligned with the socio-religious context of ASN in local government institutions.